Computational fluid dynamic analysis for solar powered water treatment device - Zawawi M.H.; Yusairah W.N.; Abidin S.Z.; Ismail I.N.; Zahari M.N. (American Institute of Physics Inc., 2023)
Solar Powered Water Treatment Device (SWAD) is an effective and affordable water treatment device using low-cost treatment materials to treat stagnant water bodies such as lakes and ponds. SWAD is an environmental friendly device as it does not attached to any power source. The objective of this project is to design and develop 3D SWAD using 3D CAD software. Other than that, the objective is to simulate and model the water flow, spatial distribution of velocity and pressure of SWAD by Computational Fluid Dynamic (CFD). CFD analysis was used to capture the efficiency of the SWAD by simulate and model the water flows, pressure and velocity. Based on the results, the maximum velocity magnitude was 2.57m/s at outlet of pipe. The velocity contour demonstrated has high speed at the pipe outlet. The pressure magnitude was in between 9246 Pa to 2609 Pa. The results of water quality parameters has proved that the water development and the direction of water flow of the SWAD can remove the pollutant efficiently. The results of vector plot, velocity contour, water flow streamline and pressure contour were effectively determined. 2018 Author(s).